Dysfunction of Thyroid and Parathyroid After Breast Cancer Radiation Therapy in Bandarabbas Omid Radiotherapy Center - Yaghoub Ashouri Taziani; Ramie Derakhshande; Leili Darvish; Mahdieh Afkhami Ardekani; Jahanbakhsh Bagherzadeh Homaei; Parisa Rabiei; Mohammad Haghparast (Disease and Diagnosis)
Background: Radiotherapy-induced hypothyroidism (HT) seems to be more frequent in breast cancer (BC) patients receiving radiotherapy to the supraclavicular field because part of the thyroid gland is included in the field. Thus, this study aimed to evaluate radiation-induced HT in patients with BC by assessing thyroid function before and 6 months after radiotherapy. Materials and Methods: In total, 27 patients undergoing three-dimensional conformal radiotherapy for BC were enrolled in this study. Thyroid-stimulating hormone (TSH), thyroxine, and triiodothyronine (T3), as well as parathyroid hormone (PTH), were measured before, on the last day of radiotherapy, and 6 months after radiotherapy. In addition, dose-volume parameters of the thyroid gland, including the volume of the thyroid gland receiving 20 Gy, 30 Gy, 40 Gy, and 50 Gy, as well as the mean dose to the thyroid, were derived from dose-volume histograms. Statistical comparisons were performed utilizing SPSS 16.0 software. The normal distribution of the data was investigated using the Shapiro-Wilk test. A paired t-test was used to compare thyroid and parathyroid function tests before and after radiation therapy (RT), and P values≤0.05 were considered statistically significant. Results: No statistically significant difference was found between thyroid and parathyroid function tests before and 6 months after the completion of radiotherapy (P>0.05). There was a significant difference only in the T3 level before and the last day of radiotherapy (P=0.027). The mean (standard deviation) thyroid dose was 15.0 Gy (6.8), and the mean (SD) value of V20-30-40-50 was 30.3% (14.8), 24.9% (14.8), 18.9% (14.2), and 7.5% (10.7), respectively. Conclusion: The findings revealed that thyroid and PTH levels did not significantly change before and 6 months after BC radiotherapy. This finding is important for both patients and healthcare providers, highlighting that HT is unlikely to be a critical factor in the management and prognosis of BC following RT.